Intelligent Clothing Design and Data Acquisition under the Scientific Graphics Programming Combined with Wearable Multisensor - Mengshu, Ding; Qistina Donna Lee, Abdullah; Salmiah, Abdul Hamid (Hindawi Publishing, 2022)
'is research focuses on the improvement of intelligent Hanfu design system’s performance. Henceforth, in the current study, anintelligent Hanfu design data acquisition system based on scientific graphics programming and wearable multisensor is designedfor the field of human body size measurement and human model reconstruction. Initially, on the basis of wearable multisensor, designoftherecognitionandanalysissystemofhumanpostureispresented.'eerrorofnine-axisinertialsensorintheprocessofcollectingdata,thedataofaccelerometer,gyroscope,andmagnetometerarepreprocessed,andtheprocessingresultsareobserved.Moreover, MATLAB programming is used for preprocessing of collected images. It is also used for grey normalization, filteringdenoising, and image sharpening. 'e advantages and disadvantages of different methods are compared experimentally. Ex-periments show that MATLAB programming is more suitable for grey normalization than histogram equalization, and localbrightness will appear in histogram equalization. After denoising the image with salt-and-pepper noise and Gaussian noise, themedianfilterandmeanfilterhavedefects.Wiener’sadaptivefilterleadstotheincreaseofnoise,andwaveletdenoisinghasthebesteffect. 'e data acquisition system of intelligent Hanfu design established in this work provides a certain direction for thedevelopment of intelligent Hanfu design.1.IntroductionIn recent years, the number of Hanfu lovers has increasedrapidly,andtheHanfuindustryhasattractedmoreandmoreattention. 'e development and progress of economy, sci-ence, and technology have promoted the development ofe-commerceplatform.Peoplearemoreandmoreinclinedtoonline shopping, and the proportion of Hanfu onlineshopping is also gradually increasing. 'erefore, for theproblem of low quality and ill-fitting of Hanfu in onlineshopping, intelligent Hanfu design can effectively designHanfuaccordingtothephysicalcharacteristicsofconsumersto make it more suitable for consumers. 'e most importantthing in intelligent Hanfu design is the construction ofhuman body data acquisition system, which can help Hanfudesign collect human body data and improve the design.Many researches have been made on human data ac-quisition at home and abroad. Chung et al. built a testplatform, including eight wearable inertial measurementunit sensors and an Android mobile device for activity dataacquisition. A long-term and short-term memory networkframework was developed to support the training of deeplearning models for human activity data obtained in the realworld and controlled environment [1]. Dickinson et al.determined the effects of collar size and collar weight on theacceleration measured by the collar mounted accelerator.'e purpose is to propose best practices for the size andweight of collars for deploying triaxial accelerometers [2].Liberadzkietal.proposedamultispectralseparationsupportmethod based on structured light to realize multidirectionaland parallel acquisition. In this method, single-frame fringeprojection is used for detailed geometric reconstruction. AnHindawiMathematical Problems in EngineeringVolume 2022, Article ID 2474047, 14 pageshttps://doi.org/10.1155/2022/2474047